A alma mortal e suas afecções: uma leitura do Timeu de Platão - Lucena, Maria Gorette Bezerra de (2014)
In this research we examine the mortal soul and its disorders (pathémata) in Plato's Timaeus, to show that in this dialogue Plato extends the concept of death (thánatos) to explain the bond (syndouménes) and the association or communion (koinonía) between the mortal soul and the body. Plato relates the notion of death to the field of philosophy, so that on the one hand, the attribute mortal indicates the composition of human body and of all physical, visible and tangible beings; and sustains the state of dissolution and corruption of these (Timaeus 42e - 43a). Whereas on the other hand it indicates the intrinsic association (koinonía) between the deadly form of the body and mind both of distinct natures. This makes us infer that the deadly attribute (thnetón) is not used by Plato to designate the death of the mortal soul génos (téns psychéns thnetòn génos, Timaeus 69 d-e). Nowhere in the passages of the Timaeus Plato says that the eidos/génos of mortal soul is an elementary being and therefore, is natural to the human body and other beings. In a kind of divine and philosophical demiurge, Plato mixes psychic and physical aspects and demonstrates that the soul of mortal eidos is stuck in the body (sôma) through the medulla (myelós) and that the bonds of every human soul is anchored (ankurôn) in the bone marrow. Thus, the mortal soul feels and vigorates all body parts and accepts the disorders (pathémata) arising from its union with Soma. This reflection helps Plato demonstrate how the body affects the soul (psyché) and how affections (páthos) and passions (tà pathé) are born. It also helps him clarify the true meaning of mortal attributes (tòn thnetón) in relation to the form of mortal soul. Hence, the mortal attribute does not express the death (thánatos) of eídos/génos of mortal humon soul. It is just a Platonic dialectics of action encountered in the psychic tendencies of each of us that explains the complex union of thánatos with psyché sôma, aimed at the formation of virtuous and righteous citizens, the sole purpose (télos) of his philosophy.